Technological Advancements in Perceived Organizational Support Enhancing Healthcare Systems Towards Sustainable Development Goals - Gathmyr, Dewi; Suhud, Usep; Herlitah, Herlitah; Hamidah, Hamidah; Safariningsih, Ratna Tri Hari; Wilson, Joseph (Pandawan, 2025)
Hospitals play a vital role in the healthcare system, with organizational support significantly influencing healthcare workers well-being and performance. This study explores the antecedents and consequences of Perceived Organizational Support (POS) in hospitals and highlights the role of technological advancements in enhancing POS. A Systematic Literature Review (SLR) was conducted to synthesize findings from recent studies on POS, focusing on key factors influencing its development and outcomes. The antecedents of POS include leadership, work conditions, and organizational policies prioritizing fairness and employee engagement. Leadership styles and supportive work environments foster trust and emotional security. The consequences of POS include improved performance, job satisfaction, and resilience, as well as reduced burnout, PTSD, and turnover intention. POS also promotes organizational citizenship behavior and work engagement. Technological advancements, such as AI and telemedicine, enhance POS by streamlining operations and improving communication. This study underscores POS critical role in achieving Sustainable Development Goals (SDGs), particularly SDGs 3 (health and well-being) and SDGs 8 (decent work and economic growth). The findings provide valuable insights for healthcare leaders and policymakers to strengthen organizational support systems, ensuring workforce sustainability and improved healthcare outcomes.